Wyniki badań sondażowych przeprowadzonych przy kościele parafialnym p.w. Wniebowzięcia Najświętszej Marii Panny i św. Jakuba Apostoła w Szadku - Antosik, Łukasz; Muzolf, Błażej; Troszczyńska-Antosik, Monika (Biuletyn Szadkowski, 2011)
A survey of parish church in Szadek under the invocation of Assumption of Our Lady and Saint James the Apostle, was done for the purposes of conservation works carried out in the church building. Archeological work was conducted in one excavation only, 2m x 1m large, situated close to the south wall of the presbytery at the level of the middle buttress. The reason for choosing this site for excavation work was that a large crack in the wall was noticed in this place. During exploration of the successive layers 13 graves were discovered. The artefacts unearthed included 137 fragments of earthenware, 23 pieces of building ceramics, 8 metal pieces, 15 fragments of window glass and two pieces of glassware. The objects found in the excavation can be dated at 13th/14th–19th centuries.